Berberine alleviates respiratory syncytial virus (RSV)-induced pediatric bronchiolitis and fibrosis via suppressing the HMGB1/TLR4/NF-κB pathway - Yang Jiao; Rui Yang (Microbiology Spectrum)
ABSTRACT Berberine exhibits antitumor, antibacterial, and antiviral properties. This study explored its therapeutic potential and molecular mechanism in respiratory syncytial virus (RSV)-induced pediatric bronchiolitis (PB). BEAS-2B cells were infected with RSV (multiplicity of infection = 0.5, 1.0, or 5.0) to establish a PB cell model. Quantitative reverse transcription PCR (qRT-PCR) quantified RSV, HMGB1, and fibrosis-related genes. MTT assay assessed cell viability, and plaque assay measured RSV titers. Western blot, immunohistochemistry (IHC), immunofluorescence, and enzyme-linked immunosorbent assay (ELISA) evaluated HMGB1 and key markers of inflammation, pyroptosis, epithelial-mesenchymal transition (EMT), and fibrosis. Flow cytometry analyzed apoptosis, while electron microscopy visualized RSV-induced pyroptotic and apoptotic changes. A PB mouse model was established by administering RSV (6.8 × 10⁶ PFU) via nasal drip in BALB/c mice. Mice were divided into six groups (n = 5 per group): blank, RSV, RSV + dimethyl sulfoxide (DMSO), RSV + berberine low dose, RSV + berberine medium dose and RSV + berberine high dose. HE staining examined lung pathology, while Western blot, IHC, ELISA, and immunofluorescence quantified HMGB1 and markers of inflammation, pyroptosis, EMT, and fibrosis. Berberine significantly reduced RSV replication, alleviated lung inflammation and fibrosis, and suppressed the HMGB1/TLR4/NF-κB pathway in both RSV-infected BEAS-2B cells and PB mice, as indicated by the downregulation of HMGB1, TLR4, p-IκBα, and p-p65. Berberine also inhibited pyroptosis (NLRP3, ASC, cleaved caspase-1, caspase-11, and GSDMD-N), EMT (Snail and N-cadherin), and fibrosis (CoL1A1, α-SMA, fibronectin, and ACTA2). Electron microscopy confirmed that RSV-induced cellular damage, including mitochondrial swelling and chromatin condensation, was alleviated by berberine treatment. These protective effects were reversed by HMGB1 overexpression and enhanced by TLR4 inhibition, indicating that berberine exerted its effects via the HMGB1/TLR4/NF-κB signaling pathway. Overall, berberine attenuated RSV-induced PB by suppressing the HMGB1/TLR4/NF-κB pathway, reducing inflammation, pyroptosis, EMT, and fibrosis in lung tissues and epithelial cells, which may be a promising remedy for RSV-induced PB.IMPORTANCEPediatric bronchiolitis caused by RSV remains a major global health challenge with limited treatment options. This study highlights berberine as a promising therapeutic agent capable of reducing RSV replication and associated lung injury. By targeting the HMGB1/TLR4/NF-κB pathway, berberine effectively attenuates inflammation, pyroptosis, EMT, and fibrosis. These findings provide a novel mechanistic insight and offer potential for the development of targeted therapies against RSV-induced bronchiolitis.